Representatives of the executive laid a wreath on the memorial to the Republic. Kautsky speaking in memory of Victor Adler. F.r.t.l.: Bracke, ?, Abramovič, Turati
Representatives of the executive laid a wreath on the memorial to the Republic. Kautsky speaking in memory of Victor Adler. F.r.t.l.: Bracke, ?, Abramovič, Turati.